Assessing Human-Fluid-Structure Interaction for the International Moth. (2016) - Banks, J.; Giovannetti, L. Marimon; Taylor, J.C.; Turnock, S.R.
Abstract: The International Moth is an ultra-lightweight foiling dinghy class. Foil deflections and dynamic sailor-induced motions are identified as two key areas relating to foiling moth performance that are currently ignored in Velocity Prediction Programs (VPP). The impact of foil deflections is assessed by measuring the tip deflection and twist deformation of a T-foil from an International Moth. The full field deformation due to an applied load is measured using Digital Image Correlation (DIC). The foil's structural properties can then be determined based on the measured structural response. The deformations are then calculated for an estimated steady sailing force distribution on the T-foil and their impact on performance is evaluated. To investigate the impact of dynamic sailor motions a system is developed that allows a sailor's dynamic pose to be captured when out on the water by determining the orientations of key body segments using inertial sensors. It is validated against measured hiking moments and is demonstrated to work out on the water whilst sailing. Both these studies pave the way towards developing a Dynamic VPP for the international Moth, which can include unsteady human and foil interactions.